Genome-wide association analysis of a stemborer egg induced “call‑for‑help” defence trait in maize - Tamiru, A.; Paliwal, R.; Manthi, S.J.; Odeny, Damaris Achieng; Midega, C.A.; Khan, Z.R.; Pickett, J.A.; Bruce, T.J. (Springer, 2020)
Tritrophic interactions allow plants to recruit natural enemies for protection against herbivory. Here we investigated genetic variability in induced responses to stemborer egg-laying in maize Zea mays (L.) (Poaceae). We conducted a genome wide association study (GWAS) of 146 maize genotypes comprising of landraces, inbred lines and commercial hybrids. Plants were phenotyped in bioassays measuring parasitic wasp Cotesia sesamiae (Cameron) (Hymenoptera: Braconidae) attraction to volatiles collected from plants exposed to stemborer Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) eggs. Genotyping-by-sequencing was used to generate maize germplasm SNP data for GWAS. The egg-induced parasitoid attraction trait was more common in landraces than in improved inbred lines and hybrids. GWAS identified 101 marker-trait associations (MTAs), some of which were adjacent to genes involved in the JA-defence pathway (opr7, aos1, 2, 3), terpene biosynthesis (fps3, tps2, 3, 4, 5, 7, 9, 10), benzoxazinone synthesis (bx7, 9) and known resistance genes (e.g. maize insect resistance 1, mir1). Intriguingly, there was also association with a transmembrane protein kinase that may function as a receptor for the egg elicitor and other genes implicated in early plant defence signalling. We report maize genomic regions associated with indirect defence and provide a valuable resource for future studies of tritrophic interactions in maize. The markers identified may facilitate selection of indirect defence by maize breeders.